Design of a low cost indoor ultrasonic intruder deterrent system with GSM based SMS notification - Mwandiambira, Bornwell (2020)
Home/ Bank/ Office security has been a major issue where crime is increasing and everybody wants to take proper measures to prevent intrusion. The project is aimed at developing the security of home against Intruders. In a case of intrusion while the user is out of the house, then the device sends SMS to the emergency number provided to it and also display it on LCD connected to it. The paper consists of a background into the area At mega 2560 microcontroller, sensing elements and GSM modem, how they are interfaced to each other and AT (Attention) commands set used in communication. This system can avoid these undesirable situations of burglary and theft. Th security system has features like changing the input password of the system and a user friendly visual and audible interfaces for the user to operate on. The main goal of this research is to aid and assist in intrusion detection and avoid criminal activities which include theft and burglary. This research insured a cost effective and practical device that can be used in the student‟s country.